2004
DOI: 10.1128/jvi.78.21.11916-11925.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Cytoplasmic Domain of ICAM-1 and Pr55 Gag Leads to Acquisition of Host ICAM-1 by Human Immunodeficiency Virus Type 1

Abstract: We have examined the molecular basis for the selective incorporation of the adhesion molecule ICAM-1 within human immunodeficiency virus type 1 (HIV-1). The process of ICAM-1 incorporation was investigated by using different ICAM-1 constructs in combination with virus capture and immunoprecipitation studies, Western blot and confocal microscopy analyses, and infectivity assays. Experiments conducted with viruses bearing a truncated version of ICAM-1 revealed that the cytoplasmic domain of ICAM-1 governs insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…We speculate that these previous observations likely represent a passive mode of incorporation. Alternatively, in the overexpression context used in these studies, a small population of ICAM-1 molecules may escape from a binding partner that would prevent specific recruitment to assembly sites and, as a result, engage in direct or indirect interactions with Gag (85). Consistent with these interpretations, a previous study showed that the amounts of ICAM-1 present on the virions correlate with the levels of ICAM-1 expression on virus-producing 293T cells (86).…”
Section: Discussionsupporting
confidence: 67%
“…We speculate that these previous observations likely represent a passive mode of incorporation. Alternatively, in the overexpression context used in these studies, a small population of ICAM-1 molecules may escape from a binding partner that would prevent specific recruitment to assembly sites and, as a result, engage in direct or indirect interactions with Gag (85). Consistent with these interpretations, a previous study showed that the amounts of ICAM-1 present on the virions correlate with the levels of ICAM-1 expression on virus-producing 293T cells (86).…”
Section: Discussionsupporting
confidence: 67%
“…Gag precursor polyprotein, which codes for all the structural proteins of HIV-1 (20,(38)(39)(40)(41), acts as a dominant actor in the process of acquisition of ICAM-1 (30). Therefore, our initial series of investigations were aimed at corroborating this observation using a simple and pertinent model of VLPs mimicking the immature virion state.…”
Section: Nucleocapsid Sp2 and P6 Gag Domains Do Not Contribute To Imentioning
confidence: 99%
“…The presence of host-derived ICAM-1 within VLPs and NL4.3-derived virus (both WT and mutated forms) was monitored by capturing viruses with immunomagnetic beads using a previously reported procedure, with slight modifications (30). In brief, streptavidin-coated magnetic beads (7.5 ϫ 10 5 beads) (Dynabeads M280; Invitrogen, Burlington, Canada) were washed once with PBS supplemented with 5% bovine serum albumin (BSA) (binding medium) using a vertical magnetic plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the connection between ICAM-1 and the cortical actin was demonstrated on one hand and that the interaction between HIV-1 Gag and filamentous actin was confirmed on the other hand, it was proposed that the insertion of Gag, actin, and ICAM-1 within nascent virions would be in the form of a multimolecular complex (9).…”
Section: Host Cell Proteins Located On Virusesmentioning
confidence: 99%